Autophagy Blockage Reduces the Incidence of Pancreatic Ductal Adenocarcinoma in the Context of Mutant Trp53 - Mainz, Laura; Sarhan, Mohamed A. F. E.; Roth, Sabine; Sauer, Ursula; Maurus, Katja; Hartmann, Elena M.; Seibert, Helen-Desiree; Rosenwald, Andreas; Diefenbacher, Markus E.; Rosenfeldt, Mathias T. (Frontiers in Cell and Developmental Biology, 2022)
Macroautophagy (hereafter referred to as autophagy) is a homeostatic process that preserves cellular integrity. In mice, autophagy regulates pancreatic ductal adenocarcinoma (PDAC) development in a manner dependent on the status of the tumor suppressor gene Trp53. Studies published so far have investigated the impact of autophagy blockage in tumors arising from Trp53-hemizygous or -homozygous tissue. In contrast, in human PDACs the tumor suppressor gene TP53 is mutated rather than allelically lost, and TP53 mutants retain pathobiological functions that differ from complete allelic loss. In order to better represent the patient situation, we have investigated PDAC development in a well-characterized genetically engineered mouse model (GEMM) of PDAC with mutant Trp53 (Trp53R172H) and deletion of the essential autophagy gene Atg7. Autophagy blockage reduced PDAC incidence but had no impact on survival time in the subset of animals that formed a tumor. In the absence of Atg7, non-tumor-bearing mice reached a similar age as animals with malignant disease. However, the architecture of autophagy-deficient, tumor-free pancreata was effaced, normal acinar tissue was largely replaced with low-grade pancreatic intraepithelial neoplasias (PanINs) and insulin expressing islet -cells were reduced. Our data add further complexity to the interplay between Atg7 inhibition and Trp53 status in tumorigenesis.